A randomized, double-blind, parallel and placebo-controlled clinical study to evaluate the efficacy and safety of KaraCalm™: a dietary supplement to support sleep and manage stress - Gersappe, Vrushali; Rajendran, Krishna; Layton, Keri; Guan, Breanna; Gupta, Ashish K.; Venkateshwarlu, Kudiganti (International Journal of Basic & Clinical Pharmacology, 2024)
Background: KaraCalm™ is a novel polyherbal formulation obtained from the combination of Valeriana officinalis extract, Passiflora incarnata extract, Ocimum sanctum extract, Ziziphus jujuba extract, Rosmarinus officinalis extract, and Nigella sativa extract. The objective of the present investigation was to assess the efficacy and safety of KaraCalm™ to manage stress and improve sleep in healthy subjects in a randomized, double-blind, placebo-controlled clinical study. Methods: A total of 60 healthy volunteers were randomized into two groups, with 30 subjects in the KaraCalm™ group and 30 in the placebo group. Participants were asked to take KaraCalm™ 500 mg or placebo once daily for 56 days. As primary outcomes, sleep analysis was performed by using Actiwatch, while stress level was evaluated with the Perceived Stress Scale (PSS) scores from baseline to the end of the study period. Serum cortisol, and hs-CRP from baseline to the end of the study period were assessed as secondary endpoints. Results: An increase in overall sleep quality was observed in the KaraCalm™ group compared to the placebo as measured by total sleep time, onset latency, wake after sleep onset minutes, and number of awakenings. There was also a reduction in PSS scores in the KaraCalm™ group from baseline to the end of the study, indicating reduced stress levels. A significant reduction in Serum cortisol and hs-C-reactive protein (CRP) levels in the KaraCalm™ group from baseline to the end of the study further supported the effectiveness of KaraCalm™ in reducing stress. There was no significant change in the safety analyses of the patients in the intervention group when assessed from the start of the study to the end. Conclusions: KaraCalm™ can be considered a safe and effective dietary herbal Supplement to reduce stress and improve sleep quality.